A felvidéki vasúthálózat Trianon és az első bécsi döntés viszonylatában - Miszlay, Zsolt (Közép-Európai Közlemények, 2011)
Hungary’s World War Two taking a role also federal, military and political brought it about on a large scale the result of a first Vienna decision in 2th November on 1938. With this decision Hungary got 1042,7 km normal track gauge railway line and 42 km narrow track gauge railway line including the area of the Felvidék. Hungary got back the Budapest–Pozsony main railway line till part of Szenc, furthermore the domestic railway system was his part again Érsekújvár, Losonc, Kassa, Ungvár, Munkács, and Beregszász. The railway system was growing whit this 8999 km long. Present lecture wishes to track it the treaty of Trianon, and the result of the first Vienna decision’s restored the situation of Felvidék railroad. We mention it as an important required information, that our maps illustrations in this lecture were nowhere published till now, it will our present lecture first.